Practice questions in Psychopharmacology Volume 1 - Sajja, Srikanth; Mortimer, Ann M.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2011)
Topics Covered Include: Development of Psychotropic Drugs Research Methodology for Drug Trials Pharmacokinetics Antidepressant Drugs Pharmacological Treatment of Psychiatric Disorders Pharmacoeconomics and Many More...
Keywords: Medicine; Psychiatry; Psychopharmacology; Psychotherapy; Medicine & Public Health; Psychopharmacology; Psychiatry; Psychotherapy; Medicine/Public Health, general